POTENSI PENGEMBANGAN DAYA TARIK WISATA DI DESTINASI PARIWISATA IKAN SAKTI SUNGAI JANIAH KECAMATAN BASO KABUPATEN AGAM - Hendri Azwar (JURNAL PENDIDIKAN DAN KELUARGA, 2017)
ABSTRACT This study aims to analyze the potential development of a tourist attraction in Tourism Destinations of Ikan Sakti Sungai Janiah Kecamatan Baso Kabupaten Agam. This study used qualitative and SWOT analysis. The data source is Head of Tourism, Youth and Sports, the Chief Manager of Tourism Destinations, Community Leaders, and tourists. The techniques of data collection were through interviews, observation, and documentation. Data were analyzed qualitatively including reduction, data presentation, and conclusions. The results showed that the potential development of tourist attraction in this tourists destination is tracking, flying fox, fishing pond, bathhouse, camping area, playground, park, packaging art such as; Randai, dances, Debus, Talempong Pacik, Pupuik, Makan Bajamba, and Martial Arts Performances. Development strategies of a tourist attraction by optimizing the natural resources that already exist, giving training in tourism awareness to the community, building cooperation with local governments, managers and the public in the packaging of a tourist attraction, improve human resources by providing training and looking for investors in the development of tourist attraction, and increasing community involvement in the management of a tourist attraction.